Mother Theresa [videorecording] ([S.l.] Petrie Productions, 1975)
A profile of the renowned saintly missionary who won the 1979 Nobel Peace Prize.
Narration, Richard Attenborough; edited by Tom Haneke.
Keywords: Teresa, Mother; Missionaries of Charity; Missions; Social work; Biography